2003
DOI: 10.1002/art.10704
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐mediated adhesion of human articular chondrocytes to cartilage

Abstract: Objective. To determine 1) the kinetics and strength of adhesion of human articular chondrocytes to a cut cartilage surface, and 2) the role of specific integrins in mediating such adhesion, using an in vitro model.Methods. Human articular chondrocytes isolated from cadaveric donors (mean ؎ SD age 38 ؎ 13 years) were cultured in high-density or low-density monolayer. Following release from culture with trypsin and a 2-2.5-hour recovery period, chondrocytes were analyzed either for adhesion to cartilage or for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 46 publications
5
60
0
1
Order By: Relevance
“…Nonetheless, ␣v␤5 integrin could be another important integrin in chondrocytes. The results of previous studies, along with the findings of the present study, consistently indicate that ␣v␤5 integrin is abundantly expressed on articular chondrocytes (19,20) and that ␣v␤5 integrin mediates chondrocyte attachment to various matrices (45,46). Therefore, it would not be surprising to find that ␣v␤5 integrin is involved in the metabolic and morphologic changes that occur in monolayer-cultured chondrocytes after plating.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Nonetheless, ␣v␤5 integrin could be another important integrin in chondrocytes. The results of previous studies, along with the findings of the present study, consistently indicate that ␣v␤5 integrin is abundantly expressed on articular chondrocytes (19,20) and that ␣v␤5 integrin mediates chondrocyte attachment to various matrices (45,46). Therefore, it would not be surprising to find that ␣v␤5 integrin is involved in the metabolic and morphologic changes that occur in monolayer-cultured chondrocytes after plating.…”
Section: Discussionsupporting
confidence: 86%
“…The activity of R-Ras increased noticeably during culture, which likely caused the increase in cell attachment via the activation of ␣v␤5 integrin. An increase in chondrocyte attachment by culture has been demonstrated previously (45,52), but the mechanism(s) of the increase have not yet been determined. This is the first study to show that the elevation of R-Ras activity might account for that phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated chondrocytes were also seeded onto a cartilage substrate and cultured to form an in vitro transplant model similar to that previously described (30,31,35). Briefly, individual cartilage sections were secured between a polysulfone tube and an annular base, creating a well, with cartilage forming the bottom surface.…”
Section: Methodsmentioning
confidence: 99%
“…After 80 minutes of adhesion, the resistance of cells to flow-induced shear stress (50% detachment) was approximately 21 Pa. 38 It was also shown that under the culture and seeding conditions studied, β1, α5β1, and αVβ5 integrins mediate human chondrocyte adhesion to cartilage. 38 It is not known if adhesion on other surfaces such as from scaffolds involves other integrins.…”
Section: Cells Stability and Scaffoldsmentioning
confidence: 92%